Analysis for Officials Granting Business License without Environmental Permits - Mohammad Chandra Bachtiar Effendi; Emy Rosnawati (Athena: Journal of Social, Culture and Society, 2025)
Criminal sanctions for licensing officials operating without environmental permits. In fact, legal violations sometimes occur when commercial permits are issued without considering environmental licensing requirements, which can harm the environment and the surrounding community. This research uses a normative legal method with a legislative approach. Secondary legal materials are the Environmental Protection and Management Law No.32/2009, and secondary legal materials are obtained from literature reviews such as legal books, research by legal experts, and journals related to environmental permits. Conclusions are drawn using deductive reasoning